In Memory of Matryona and Valerij Sotkayarvi of Jona - Robinson, Mike (ARCTIC, 1998)
Director of the Arctic Institute of North America, Mike Robinson, pays tribute to two Sami who were recently murdered in their home in the village of Jona. The Arctic Institute and Sami were partners working together on traditional land-use and occupancy maps of the Sami in the Kola Peninsula over the past three years, and these two individuals had been deeply involved in this project. Their deaths are evidence of the deep social and economic problems experienced in this region and it is hoped that their experience will not be forgotten. "They were both wonderful examples of the Sami way, and their generosity of spirit lives on in Jona, a small Sami village that has weathered the Russian Revolution of 1917, the purges of Stalin, the ravages of Nazi attacks, the collapse of Communism, and the arrival of perestroika and glasnost. I think Jona will continue as always, and the great forces of history will ebb and flow around and about Sami reindeer herders who have not lost either their courage or their stewardship relations with the land."